Tracheostomy manipulations: Impact on tracheostomy safety - Alexandra G Espinel; Kelly Scriven; Rahul K Shah (Wiley, 2019)
Abstract Importance Tracheotomy is one of the riskiest procedures for composite morbidity within pediatric otolaryngology. During the postoperative period, each time the tracheostomy tube is manipulated, there is opportunity for morbidity (e.g. a patient is vulnerable to accidental decannulation and airway loss). Objective To identify areas of improvement in caring for "fresh tracheostomy" patients by determining the number of times a tracheostomy tube is manipulated from placement until discharge. The hypothesis is that the more a tracheostomy is manipulated, the higher probability of morbidity. Methods A quality improvement initiative was conducted to map the care of patients who underwent tracheostomy placement over 12 months. Tracheostomy care and manipulation by all providers were reviewed. Complications, wound care, and respiratory treatments were also evaluated. Results Patients were hospitalized for an average of 39 days (7-140) following tracheostomy. The first tracheostomy tube change occurred on average 6 days (5-10) following placement. Tracheostomy tubes were manipulated an average of 6 (2.5-11.9) times a day to amount to 216 (51-1091) times between placement and discharge. Bedside nurses and respiratory therapists were responsible for 95% of these actions; physicians accounted for 4%. There were 6 tracheostomy related complications. Three were accidental decannulations resulting in cardiopulmonary arrest. One of these caused long term patient morbidity. Patients with more than 4 manipulations per day during the 2 weeks following tracheostomy tube placement, were more likely to have a tracheostomy related complication than those with less than 4 (OR: 12.5; 95% CI: 1.2-130.6; P = 0.0349). Interpretation While uncommon, complications related to tracheostomy can have serious long term effects and at best prolongs length of stay for patients. Reducing the number of tracheostomy manipulations may provide safer postoperative care ultimately reducing morbidity and potentially mortality; children on average have 6 tracheotomy manipulations/day with only 2% being by the physician.